2023
DOI: 10.2174/1570159x21666221220155455
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Hippocampal Neurogenesis in Autism Spectrum Disorder: Pathogenesis and Therapeutic Implications

Abstract: Autism spectrum disorder (ASD) is a cluster of heterogeneous neurodevelopmental condi- tions with atypical social communication and repetitive sensory-motor behaviors. The formation of new neurons from neural precursors in the hippocampus has been unequivocally demonstrated in the dentate gyrus of rodents and non-human primates. Accumulating evidence sheds light on how the deficits in the hippocampal neurogenesis may underlie some of the abnormal behavioral phenotypes in ASD. In this review, we describe the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 183 publications
0
13
0
Order By: Relevance
“…Therefore, changes in the E-I balance that are suggested to occur in neurodevelopmental disorders (Gao and Penzes, 2015;Kenny et al, 2022) may influence physiological generation of SWRs. Interestingly, previously accumulated evidence shows that FXS-associated neurobiological changes are brain region-specific (Anagnostou and Taylor, 2011;Varghese et al, 2017;Fetit et al, 2021) and hippocampus is among the brain regions that are affected by the loss of FMRP (Banker et al, 2021;Liu et al, 2022). However, the hippocampus is a functionally heterogeneous structure in both health and disease (Bannerman et al, 2014;Strange et al, 2014) and the dorsal and the ventral hippocampus are differently implicated in neuropsychiatric and neurodevelopmental disorders; reviewed by Sahay and Hen (2007), Tanti and Belzung (2013), Bartsch and Wulff (2015), Gulyaeva (2019), and Bakoyiannis et al (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changes in the E-I balance that are suggested to occur in neurodevelopmental disorders (Gao and Penzes, 2015;Kenny et al, 2022) may influence physiological generation of SWRs. Interestingly, previously accumulated evidence shows that FXS-associated neurobiological changes are brain region-specific (Anagnostou and Taylor, 2011;Varghese et al, 2017;Fetit et al, 2021) and hippocampus is among the brain regions that are affected by the loss of FMRP (Banker et al, 2021;Liu et al, 2022). However, the hippocampus is a functionally heterogeneous structure in both health and disease (Bannerman et al, 2014;Strange et al, 2014) and the dorsal and the ventral hippocampus are differently implicated in neuropsychiatric and neurodevelopmental disorders; reviewed by Sahay and Hen (2007), Tanti and Belzung (2013), Bartsch and Wulff (2015), Gulyaeva (2019), and Bakoyiannis et al (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MOR modulates the hippocampal neurogenesis, mediating a negative opioid effect, whereas a positive effect can be seen in MOR null knock-out mice [79, 80]. The animal models of ASD present an impaired hippocampal neurogenesis, possibly explaining some of the behavioral phenotypes of the disorder [81]. Our findings on MOR availability could relate to these forementioned behavioral impairments and aberrant modulation of the DMN and the possibly impaired hippocampal neurogenesis in ASD.…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, our results showed that BTBR animals had decreased NGF and BDNF expression levels in HIPP, a brain region in which such neurotrophins are mainly present [ 88 ]. Accordingly, hippocampal BDNF and NGF deficiency has been associated with ASD development [ 89 , 90 ], however results are contrasting, since BDNF brain levels fluctuations have been reported in response to several known, such as brain areas and age, and unknown factors [ 91 ]. In addition, NGF levels were reduced also in AMY, a brain region in which NGF signalling has been linked to stress, reward and neuroprotection [ 92 ].…”
Section: Discussionmentioning
confidence: 99%